Labor Supply Elasticity in the Unconditional Basic Income System: Data Sources and Methodological Issues - Specianova, Jitka (European Scientific Journal, ESJ, 2018)
This study deals with five sources of data that may help to answer the question of how labor supply would respond to the introduction of unconditional basic income. Research of lottery winners’ labor supply and the results of field experiments, in which the behavior of households who have received a regular unconditional income for a limited time period was observed and is then investigated and discussed. Results of the laboratory experiment, the estimates of microsimulation models, and the results of the opinion polls are also examined. The surveyed data sources show mainly a slight decline in labor supply. However, none of these data were collected in situations that would fully correspond with the expected conditions of decision-making that would occur with the basic income. Any results derived from them therefore need to be considered with caution.